Lifestyle Pattern and Knowledge about Diabetes Mellitus (Medicine Today, 2019)
Introduction:The aim of the present study was to assess the pattern of lifestyle and knowledge about diabetes mellitus among type 2 diabetic patients at two tertiary level hospitals in MymensinghMaterials and Methods: A descriptive, cross sectional study was conducted from July 2015 to December 2015 among 300 patients attending at Medicine outpatient department of the Community Based Medical College Hospital and Endocrine outpatient department of the Mymensingh Medical College Hospital after obtaining requisite consent from the patients. Data were collected through the interviewing of the patients. The collected data were entered into the computer and analyzed by using SPSS version 20.1. The study was approved by the institutional ethical committee.Results: In a pool of 300 type 2 diabetics, Most of the patients (57.3%) belonged to the middle age group 41-60 years. More than half of the respondents were female (n=223, 74.3%). 97% patients were found to have knowledge about timing of dose regimen. Majority of patient’s (35.7%) knowledge about hypoglycemia was poor. The rate of adherence to diet was 51%. The rate of adherence to exercise was 68.3%.Conclusion: Majority of type 2 DM patients displayed optimal level of diabetes knowledge. There was a high rate of non adherence to diet and exercise recommendations by patients suffering from type 2 diabetes mellitus. So continuous patient education and awareness program are required.Medicine Today 2019 Vol.31(2): 102-104